Mejora del nivel de servicio del proceso productivo de Gamma Plast a través de la implementación de técnicas de Lean Manufacturing - Llerena Zúñiga, Vanessa Julissa (2021)
In this research, the analysis of the plastic bag production process of the company Gamma Plast will be presented, which offers tailored products according to the client's needs with the characteristic of being more functional, profitable, and sustainable for the environment. The vision of this organization is to be a leading company, noted for its high quality, innovation, and customer service. The company under study presents problems regarding the delivery time of the orders, since there are processes that cause unnecessary losses of time, as well as the lack of planning. This is reflected in a low service level, not complying with scheduled orders. For this reason, it is proposed to increase the service level through the implementation of Lean Manufacturing techniques, seeking to reduce downtime and optimize the production process. A qualitative and quantitative investigation will be carried out with the data and observations collected. Additionally, the research will estimate the increase in the service level generated by the implementation of lean techniques, as well as the projected technical, economic, and social benefits. In this way, the positive impact generated on the profitability and competitiveness of the company is projected.